A new small bent-toed gecko of the genus Cyrtodactylus (Squamata: Gekkonidae) from the lower slopes of Mount Tambora, Sumbawa Island, Indonesia - Riyanto, Awal; Mulyadi, Mulyadi; Mcguire, Jimmy A.; Kusrini, Mirza D.; Febylasmia, Febylasmia; Basyir, Irfan Haidar; Kaiser, Hinrich (Zootaxa, 2017)
We describe the sixth species of bent-toed gecko from the Lesser Sunda Islands, Indonesia. This species was first collected on the banks of the Oi Marai River on the low northern slopes of Gunung (Mount) Tambora on Sumbawa Island. The new species is differentiated from Greater Sunda Islands (including Sulawesi) and Lesser Sunda Islands congeners by having the following unique combination of characters: (1) two scales between the second pair of postmentals in contact with the first pair; (2) dorsal surface of antebrachium tuberculate; (3) no tubercles on dorsal surface of brachium; (4) dorsal surfaces of thigh and crus tuberculate; (5) 18 irregularly aligned, longitudinal rows of keeled tubercles at midbody; (6) 26–27 paravertebral tubercles; (7) 40 ventral scales between indistinct ventrolateral folds; (8) 16–17 fourth-toe subdigital scales; (9) a continuous enlarged precloacal and femoral scales present, with the enlarged femoral scales arranged in three rows; (10) males with five to six precloacal pores, with four larger pores situated in a short groove; (11) femoral pores absent in both sexes; (12) lack of transversely enlarged subcaudal scales; and (13) 7–9 irregular, paired black blotches on the body.